ANALISIS YURIDIS PEMBINAAN MASYARAKAT OLEH KEPOLISIAN TERHADAP PENINGKATAN PARTISIPASI WARGA DALAM PROGRAM KEAMANAN LINGKUNGAN - Wijaya, Mochamad Fillakhiya Atma; Cornelis, Vieta Imelda; Hamdani, Fathul (Gapenas Publisher, 2025)
This study aims to analyze the effect of community development by the police on increasing citizen participation in neighborhood watch programs in Windurejo Village, Kutorejo District. The method used is a juridical-empirical approach with interview, observation, and documentation study techniques. The results show that the active role of Bhabinkamtibmas in community development has a significant contribution in fostering legal awareness and citizen involvement in security activities. The success of the program is determined by factors such as personnel competence, operational facilities, support from community leaders, and synergy with the village government. However, there are also obstacles such as limited personnel and cultural constraints. This study recommends institutional strengthening, capacity building for officers, and a local participatory approach in community development programs to create sustainable environmental security